Estimation of Potential GDP and output Gap. Comparative Perspective - Dorin Măntescu; Dan-Tudor Lazăr (Amfiteatru Economic)
The purpose of the analysis is to assess the impact of the crisis on the potential output and output gaps, to study their evolution by using a comparative approach for a sample of EU countries that were in majority included recently in financial assistance and macroeconomic adjustment programmes. The potential GDP growth rates calculated using the Cobb Douglas production function and Hodrick-Prescott methodology, decelerated substantially across the board in the countries studied once the international economic and financial crisis hit, recording even negative rates of growth in Cyprus, Greece, Portugal, Italy and Spain. In addition to the specific factors that characterise each country, there is a series of common features that will affect the developments of the potential GDP on a long-term basis, such as the increase of global risk aversion correlated with the reduction of the banking exposures, the slow economic recovery in the EU, and last but not least the incoming ageing process, which will exert an additional negative impact on the growth potential of the EU member states. The article makes a series of economic policy recommendations to promote key measures aiming to increase the flexibility of the goods, services, and labour markets, to improve the prioritisation of public expenditures especially capital spending, and to improve the management of the public assets including real estate and public buildings by promoting a mix of measures including privatisation, monetisation and a wider involvement of the private sector in their management.